PENGARUH KUALITAS PIMPINAN DAN KOMPENSASI TERHADAP KEPUASAN KERJA KARYAWAN - Susanto, Edi (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2024)
The quality of a leader can be measured from various aspects that include abilities, attitudes, and behaviors shown in managing the company, and are appreciated directly by employees with their satisfied attitude. In addition to the quality of leadership, adequate employee compensation will provide satisfaction. This study aims to analyze and explain the influence of leadership quality and compensation on employee job satisfaction. The method used in this study is descriptive with a quantitative approach. The data collection method in this study is a questionnaire in the form of a statement that the respondents must choose. The population and sample of this study amounted to 50 people, all of whom were employees of CV Agung Dipo Persada, Sukabumi Regency. The results of the study explained that there was a significant influence of leadership quality and compensation on job satisfaction, where the influence was 53.5% while 46.5% was influenced by variables outside this study.